23 Diversity Of Macrophage Signatures Across A Spectrum Of Supraspinatus Pathology. (5th September 2014) - Dakin, Stephanie G; Martinez, Fernando O; Wells, Graham; Yapp, Clarence; Carr, Andrew
Abstract : Introduction: Inflammation is increasingly recognised as an important contributor to the development of tendon pathology. 1, 2 Macrophages (Mϕ) are key orchestrators of inflammation and fibrosis in connective tissues, yet little is known about their phenotype in pathological human tendons. The aim of this study was to characterise Mϕ signatures in samples of tendinopathic and torn human supraspinatus. We hypothesised that Mϕ signatures would exhibit diverse profiles throughout the spectrum of tendon pathology. Methods: Normal and tendinopathic supraspinatus were collected via ultrasound guided biopsy performed under local anaesthetic. Torn supraspinatus was collected after routine surgical debridement of the torn tendon. Mϕ were identified as CD68 + cells in formalin fixed paraffin embedded sections by immunohistochemistry. Subsequently, quadruple immunofluorescent labelling and confocal microscopy was performed to better characterise Mϕ protein signatures. To identify genes associated with Mϕ activation status, quantitative real time PCR for chemokines, cytokines and Mϕ markers was performed in samples of normal subscapularis (n = 2) and torn supraspinatus (n = 11). Results: There were significantly increased numbers of CD68 + stained cells in tendinopathic (p < 0.01) and torn (p < 0.01) supraspinatus compared to normal samples. The level of expression of genes associated with macrophage activation in torn supraspinatus showed distinct alterations at different pathological stages compared to normal subscapularis. Mϕ in small-medium sized tears (1–3 cm) exhibited a complex heterogeneous signature, with genes from LPS, IFNγ, glucocorticoid (GC) and IL-4 signalling pathways represented. In contrast, the Mϕ gene signature of large-massive tears (3–5 cm) was more representative of IL-4 and glucocorticoid signalling pathways (Table 1). Immunofluorescent labelling of tendon sections supported these findings, with a mixed Mϕ signature in tendinopathic and small-medium tears (IDO high IRF5 high CD163 high CD206 low ) and a glucocorticoid/IL-4 signature (CD163 high CD206 high ) in massive tears. Discussion: These data highlight the complexity and diversity of Mϕ signatures in supraspinatus tendons throughout the spectrum of pathology. We propose that Mϕ signatures in pathological supraspinatus tendons are implicated in driving the development of chronic inflammation and the formation of a fibrotic repair. References: 1 Dakin, et al . PLoS ONE . 2012;7(2):e32333 2 Dakin, et al . Vet Immunol Immunopath . 2014;158(3–4):21–127